A Remark on Configuration Spaces of Two Points. Issue 2 (11th April 2018) - Raptis, George; Salvatore, Paolo
Abstract: We prove a homotopy invariance result for a certain covering space of the space of ordered configurations of two points in M × X where M is a closed smooth manifold and X is any fixed aspherical space which is not a point.